Development of the Hierarchical Production System Using the Modularized Design of Group Plan Product - HOTTA, Tadaaki; KAMODA, Hiroki; NAKATSUKA, Nobuo; FUKUDA, Yoshiro; SUGAWA, Shigetoshi (Transactions of the Japan Society of Mechanical Engineers Series C, 2007)
It is called for that development of the efficient production system in large variety and small volume manufacturing carries out simultaneous solution of the complicated demand of a product kind, quality, cost, and delivery. Since only the person experienced in development of a production system can carry out subject solution, modeling of the production system which is economical by general purpose large variety and small volume production has not been completed. In order to solve these subjects, the product application is limited first, and a functional module is defined paying attention to the product function of the product and a product design and the modularized design of the manufacturing process are performed. This production system consist of function quality completed production which completes the functional quality which used this process module as the base is performed and the mixed and synchronized production system or the demand synchronized novel production system. The wide variety and small volume production system by which the knowhow of a production systems configuration corresponded to quality, cost, and delivery flexibly with constituting a module hierarchical at least can be offered.